2011
DOI: 10.1002/etc.509
|View full text |Cite
|
Sign up to set email alerts
|

Effects of time-variable exposure regimes of the insecticide chlorpyrifos on freshwater invertebrate communities in microcosms

Abstract: The present study compared the effects of different time-variable exposure regimes having the same time-weighted average (TWA) concentration of the organophosphate insecticide chlorpyrifos on freshwater invertebrate communities to enable extrapolation of effects across exposure regimes. The experiment was performed in outdoor microcosms by introducing three different regimes: a single application of 0.9 µg active ingredients (a.i.)/L; three applications of 0.3 µg a.i./L, with a time interval of 7 d; and contin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 38 publications
1
14
0
Order By: Relevance
“…The results suggest that long-term effects can be assessed by comparing TWA rather than peak concentrations, even if the dynamics of the pulses are different. Zafar et al (2011) also found similar relationships between long-term effects and TWA concentrations for most invertebrate species exposed to chlorpyrifos in microcosm under different exposure profiles with the same TWA concentration. They also concluded that for the applied combination of concentration dynamics, the TWA concentration was a more adequate predictor for long-term risks of chlorpyrifos for most species than the peak concentration.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…The results suggest that long-term effects can be assessed by comparing TWA rather than peak concentrations, even if the dynamics of the pulses are different. Zafar et al (2011) also found similar relationships between long-term effects and TWA concentrations for most invertebrate species exposed to chlorpyrifos in microcosm under different exposure profiles with the same TWA concentration. They also concluded that for the applied combination of concentration dynamics, the TWA concentration was a more adequate predictor for long-term risks of chlorpyrifos for most species than the peak concentration.…”
Section: Discussionmentioning
confidence: 66%
“…This followed a similar microcosm study with the insecticide chlorpyrifos, which concluded that for most species, but not for all, the TWA concentration was more important than the peak concentration in explaining the longer-term effects (Zafar et al 2011). The aim of the present study was to compare the effects of four different exposure regimes (two chronic, maintained exposure profiles, one repeated pulsed, and one single pulsed exposure regime) for the fungicide azoxystrobin.…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…Since the publication of the Giesy et al review, results of several cosm studies of CPY have featured prominently in comparisons of cosm studies, single-species laboratory toxicity tests, and regulatory benchmarks across classes of insecticides (Brock et al 2000(Brock et al , 2006Maltby et al 2005 ;van Wijngaarden et al 2005b ). Several newer cosm studies have broadened the scope of conclusions about chlorpyrifos effects on aquatic communities to a wider range of locations and environmental conditions (Daam et al 2008a , b ;López-Mancisidor et al 2008a , b ;van Wijngaarden et al 2005a ;Zafar et al 2011 ). The body of evidence from cosm studies is consistent in supporting the conclusion that concentrations of 0.1 μg CPY L −1 or less cause no ecologically signifi cant effects on aquatic communities.…”
Section: Evidence From Microcosms and Mesocosmsmentioning
confidence: 99%
“…In further studies, macrophyte-dominated outdoor Dutch ditch cosms were treated with CPY under three different exposure regimes: a single application of 0.9 μg L −1 , three applications of 0.3 μg L −1 at 7-d intervals, and continuous application of 0.1 μg L −1 for 21 d using a pump (Zafar et al 2011 ). The three exposure regimes were designed to produce similar 21-d time-weighted averages of 0.1 μg L −1 .…”
Section: Evidence From Microcosms and Mesocosmsmentioning
confidence: 99%